Modeling the risk process in the XploRe computing environment - Rafał Weron; Krzysztof Burnecki (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
A user friendly approach to modeling the risk process is presented. It utilizes the insurance library of the XploRe computing environment which is accompanied by on-line, hyperlinked and freely downloadable from the web manuals and e-books. The empirical analysis for Danish fire losses for the years 1980-90 is conducted and the best fitting of the risk process to the data is illustrated.
Keywords: 330